Variationsrechnung: 29.7. bis 4.8.1984 - Frehse, Jens; Jäger, Willi; Tomi, Friedrich (Tagungsbericht, 1984)
H. D. Alber, Bonn; G. Anzellotti, Povo; A. Bensoussan, Paris; R. Böhme, Bochum; G. Dziuk, Aachen; K. Ecker, Heidelberg; J. Eells, Coventry; R. Finn, Stanford; M. Fuchs, Düsseldorf; J. Frehse, Bonn; C. Gerhardt, Heidelberg; M. Grüter, Düsseldorf; E. Heinz, Göttingen; S. Hildebrandt, Bonn; E. Hölder, Mainz; W. Jäger, Heidelberg; J. Jost, Bochum; J. Kampmann, Bochum; H. Kaul, Tübingen; B. Kawohl, Erlangen; Kröner, Bonn; R. Landes, Bayreuth; S. Luckhaus, Heidelberg; M. Meier, Bonn; L. Modica, Pisa; U. Mosco, Rom; J. Nečas, Prag; N. Quien, Heidelberg; F. Sauvigny, Clausthal-Zellerfeld; K. Schüffler, Düsseldorf; C. G. Simader, Bayreuth; G. Ströhmer, Aachen; M. Struwe, Bonn; Ursula Thiel, Heidelberg; P. Tolksdorf, Bonn; Friedrich Tomi, Heidelberg; A. J. Tromba, Santa Cruz; G. Vidossich, Trieste; W. von Wahl, Bayreuth; H. Wente, Toledo; M. Wiegner, Bayreuth